2000
DOI: 10.1021/es990530z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Particles from a Current Technology Heavy-Duty Diesel Engine

Abstract: The physical properties, chemical properties, and morphology of particles from a current technology diesel engine run under steady-state conditions were determined during five campaigns across three calendar years. Concentrations of particulate matter, NO x , HC, CO, and CO 2 measured at a fixed sampling position were found to be repeatable between different campaigns. However, particle size distributions and number concentrations were significantly affected by dilution conditions. Particle density, estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(127 citation statements)
references
References 20 publications
11
113
1
2
Order By: Relevance
“…For example, particlebound PAHs freshly emitted from combustion of liquid fossil fuel are mainly distributed in the ultrafine fractions (Miguel et al, 1998;Shi et al, 2000;Phuleria et al, 2006), but unimodal size distributions of PAHs peaking at large particle sizes have been observed from rice straw and corn straw burning, which often proceeds at lower temperatures than combustion of liquid fossil fuel (Hays et al, 2005;Li et al, 2007;Zhang et al, 2011). The size distributions of PAHs in winter in Guangzhou (Figs.…”
Section: Particle Size Distribution Of Pahsmentioning
confidence: 99%
“…For example, particlebound PAHs freshly emitted from combustion of liquid fossil fuel are mainly distributed in the ultrafine fractions (Miguel et al, 1998;Shi et al, 2000;Phuleria et al, 2006), but unimodal size distributions of PAHs peaking at large particle sizes have been observed from rice straw and corn straw burning, which often proceeds at lower temperatures than combustion of liquid fossil fuel (Hays et al, 2005;Li et al, 2007;Zhang et al, 2011). The size distributions of PAHs in winter in Guangzhou (Figs.…”
Section: Particle Size Distribution Of Pahsmentioning
confidence: 99%
“…A number of articles and reports have been published regarding the contribution of traffic to OC and EC in Europe and the USA (Kerminen et al, 1997;Miguel et al, 1998;Fraser et al, 1999;Moosmüller et al, 2000;Shi et al, 2000;Kohler et al, 2001;Ruellan et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The OC/EC varied from 9.5 to 0.9 and from 5.7 to 1.4 at 2125 and 2690 r$min -1 , respectively. Shi et al investigated the particle carbon composition at 25%, 50%, and 100% load at two constant engine speeds on a turbocharged DI engine [3]. In that study, the OC and EC in PM were determined by measuring the emissions of CO 2 produced from samples burnt in pure oxygen within a programmable furnace.…”
Section: Pm Sampling and Composition Analysismentioning
confidence: 99%
“…Similar behavior of OC/EC was reported by Ålander et al [4], who showed that the OC/EC of particles from a DI engine decreased with increasing Although it is difficult to compare the results of OC and EC measured by different methods, the variation of OC/EC with engine load was consistent. Shi et al suggested that dilution condition had a greater influence on the OC fraction due to condensation of semivolatile organic compounds [3]. The OC fraction in PM mostly consists of condensed volatile organic compounds which are formed during the cooling of soot.…”
Section: Pm Sampling and Composition Analysismentioning
confidence: 99%
See 1 more Smart Citation